The Challenges of Islamic Organizations in Promoting Moderation in Indonesia - Hasse Jubba; Jaffary Awang; Siti Aisyah Sungkilang (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Islamic moderation has become a strategic agenda in Indonesia, yet the threats that can slow its implementation are often left implicit. Two leading Islamic organisations, Muhammadiyah and Nahdlatul Ulama (NU), place moderation at the core of their missionary vision to foster a tolerant, open, and civilised society. This paper examines the challenges of realising Islamic moderation in Indonesia, focusing on initiatives associated with Muhammadiyah and NU. Using a qualitative design, the study combines in-depth interviews with organisational figures from both Muhammadiyah and NU with document-based analysis of organisational narratives and relevant written sources. The interview and documentary materials are analysed interpretively to identify recurring patterns in how moderation is articulated and contested. The findings indicate that a major obstacle is the growing prominence of conservative groups, which increasingly gain wide space. This conservative turn is accompanied by weakening respect for other groups and a tendency to resist Islamic groups outside one’s own circle. By making explicit how the rise of conservative groups constrains moderation work within mainstream Islamic organisations and shapes social recognition dynamics, this study contributes an evidence-based explanation of why moderation efforts can stall even when moderation is embedded in organisational missions.